2009
DOI: 10.1111/j.1439-0426.2008.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and reproduction of the black scorpionfish,Scorpaena porcus(Pisces, Scorpaenidae), on the Black Sea coast of Turkey

Abstract: SummaryAge, growth and reproduction of the black scorpionfish, Scorpaena porcus were studied in specimens from the coast of the Sinop Peninsula (Black Sea) between March 2002 and April 2003 in order to characterize these population parameters in comparison to specimens from populations of nearby regions. A total of 1086 specimens was captured by beam trawl at the depths between 0 and 30 m. The total number of females (510) was significantly higher than that of males (373). Total length of males and females ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 9 publications
7
33
0
Order By: Relevance
“…The finding that males of S. cardinalis grow significantly faster in terms of length and attain greater sizes than do females is in contrast to the results for other similar-sized species within the genus. It is reported by Bilgin and Ç elik (2009) and Love et al (1987) that females grow larger, more quickly and have longer life spans than do males for S. porcus and S. guttata, respectively. In contrast, La Mesa et al (2005) reported that females of the much smaller species S. maderensis attain smaller maximum sizes than do males.…”
Section: Age and Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding that males of S. cardinalis grow significantly faster in terms of length and attain greater sizes than do females is in contrast to the results for other similar-sized species within the genus. It is reported by Bilgin and Ç elik (2009) and Love et al (1987) that females grow larger, more quickly and have longer life spans than do males for S. porcus and S. guttata, respectively. In contrast, La Mesa et al (2005) reported that females of the much smaller species S. maderensis attain smaller maximum sizes than do males.…”
Section: Age and Growthmentioning
confidence: 99%
“…In S. porcus and S. guttata, where females grow larger than males, both sexes have similar GSI values (Bilgin and Ç elik 2009;Love et al 1987). S. guttata is known to form large spawning aggregations offshore (Love et al 1987) where it may be advantageous to produce large quantities of sperm.…”
Section: Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22, 10.86, 11.50, 12.77 and 14.05 cm for S. solea, respectively. Considering the other species caught by the trammel nets, the proportion of scorpion fish under the size at first maturation (17.5 cm TL) (Bilgin and Çelik, 2009) is between 86.9% and 95.4% and for sole, the proportion under the size at first maturation (15.2 cm TL) (Türkmen, 2003) varies between 57.9% and 76.6%. In this study, a large proportion of non-target caught species were under the size at first maturation or minimum allowable catch size.…”
Section: S Porcusmentioning
confidence: 99%